2015
DOI: 10.1007/s11051-015-2917-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of lycopene-loaded lipid-core nanocapsules: physicochemical characterization and stability study

Abstract: The objective of this study was to develop lycopene-loaded lipid-core nanocapsules (Lyc-LNCs) by the interfacial deposition of preformed poly(e-caprolactone) (PCL). Lyc extract (93.9 %) was obtained from tomatoes, and the organic phase was prepared with polymer (PCL), caprylic/capric triglycerides, sorbitan monostearate, and Lyc in a mixture of acetone and ethanol under magnetic stirring at 40°C. The organic phase was injected into an aqueous phase containing polysorbate 80, and the suspension was concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
14
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 40 publications
10
14
1
10
Order By: Relevance
“…Similar values were found by Santos et al (2015), that obtained lycopene entrapped in lipid-core nanocapsules with the PCL as wall material, the mean diameter (D 4,3 ) of these nanocapsules was 153 nm with a span value of 1.32. Contri et al (2013) researched alternatives (Brazil nut, sunflower seed, olive, rose hip, grape seed, and carrot oils) to replace the oil core of the Eudragit RS100® nanocapsules often made with capric/caprylic triglycerides and observed that the nanocapsules made with alternative oils presented a higher size (280 nm) and span value (2.50) than those made with capric/caprylic triglycerides.…”
Section: Particle Diameter and Zeta Potentialsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar values were found by Santos et al (2015), that obtained lycopene entrapped in lipid-core nanocapsules with the PCL as wall material, the mean diameter (D 4,3 ) of these nanocapsules was 153 nm with a span value of 1.32. Contri et al (2013) researched alternatives (Brazil nut, sunflower seed, olive, rose hip, grape seed, and carrot oils) to replace the oil core of the Eudragit RS100® nanocapsules often made with capric/caprylic triglycerides and observed that the nanocapsules made with alternative oils presented a higher size (280 nm) and span value (2.50) than those made with capric/caprylic triglycerides.…”
Section: Particle Diameter and Zeta Potentialsupporting
confidence: 89%
“…During the cold storage, the pH values of the formulations of the BALNs and BNs declined from 3.17 ± 0.03 to 2.95 ± 0.05 at day 100 (BALNs) and from 5.50 ± 0.12 to 4.25 ± 0.20 at day 100 (BNs). Santos et al (2015) conducted a study with the same technique of the present work for the production of the nanocapsules, they worked with lycopeneloaded lipid-core nanocapsules (85 μg/mL) stored at 25°C and also found a reduction in pH values from 6.01 ± 0.04 to 5.60 ± 0.02 during the storage (28 days).…”
Section: Phmentioning
confidence: 91%
“…The nanoencapsulation provide more stability of these pigments in the presence of oxygen, heat, and light, which, in general, improves the stability, solubility, and bioavailability of encapsulated species and promotes its controlled release. [26][27][28] The nanoencapsulation of β-carotene presents an alternative for greater use of carotenoid, the encapsulation of this pigment using poly-ɛ-caprolactone (PCL) with oil nucleus, and presents high encapsulation efficiency, able to provide greater retention and stability when subjected to thermal treatments or light presence. 26,29 In this context, β-carotene may represent an excellent natural compound for addition in biodegradable films and the nanoencapsulation may be a promising technique to increase the solubility and stability of this carotenoid, which to date have not been evaluated for addition in films under nanometer scale.…”
mentioning
confidence: 99%
“…The higher acidity may be associated with ionization of the functional groups present on the polymer chains of PCL, for example, the terminal carboxylic groups, which are present in the polymer, lowering the pH. 14,37,39 The PCL-nanoparticles presented negative zeta potentials, ranging from −19.7 to −33.8 mV (UNSP80 and NCP80, respectively). The negative charge is due to the PCL polymer and surfactant Lipoid S45 ® .…”
Section: Technological Evaluation Of Quinine-loaded Nanocapsulesmentioning
confidence: 99%
“…42 These lipids are ionized at pH 7.0 to induce a negative surface charge on nanoparticles, which contributes to their stability. 43 The PCL polymer also influences the negative zeta potential of nanoparticles due to the presence of ester groups and the polymer, based on the values previously described for formulations prepared with this polymer 34,39,44,45 and the influence of P80-coating, through the particle by steric stabilization. 46,47 In this study, PCL-NS presented a zeta potential less than that of PCL-NC, suggesting that capric/caprylic triglycerides also influence the zeta potential, since the organization of these nanostructures differs.…”
Section: Technological Evaluation Of Quinine-loaded Nanocapsulesmentioning
confidence: 99%